2015
DOI: 10.1186/s13104-015-1406-3
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and predictors of immunologic recovery in HIV infected patients

Abstract: BackgroundAlthough anti-retroviral therapy has generally improved the survival of HIV infected patients in many developing countries including Ghana, specific socio-demographic factors could still influence outcome of treatment. This study was designed to identify patient-specific factors that could influence the immune recovery of absolute CD4 count in HIV infected patients.FindingsHospital records were extracted from two health facilities in Ghana. The impact of socio-demographic factors type of ART and base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…This supports the most recent WHO guidelines, which advocates the initiation of ART for all HIV infected individuals regardless of CD4 count [1]. Similar to other published studies [14,33,35,36], we have shown that proportionally, immunological recovery was highest in patients who had begun treatment with a ‘low’ (<100 cells/ mm 3 ) count at baseline. However, despite showing the highest relative increase in CD4 recovery, patients in the ‘low’ group achieved lower CD4 peaks than those with higher baseline groups.…”
Section: Discussionsupporting
confidence: 91%
“…This supports the most recent WHO guidelines, which advocates the initiation of ART for all HIV infected individuals regardless of CD4 count [1]. Similar to other published studies [14,33,35,36], we have shown that proportionally, immunological recovery was highest in patients who had begun treatment with a ‘low’ (<100 cells/ mm 3 ) count at baseline. However, despite showing the highest relative increase in CD4 recovery, patients in the ‘low’ group achieved lower CD4 peaks than those with higher baseline groups.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent findings were reported from Tanzania (AOR = 4:1, (1.6-10.4), P = 0:003) [39], Uganda [41], and Bahir Dar, Ethiopia (AOR = 1:90, 95% CI: 1.41-2.56, P = 0:001) [24]. Contrasting finding from our study was reported from Asella, Ethiopia [42] that indicated HAART regimen variability was not significantly associated Journal of Immunology Research with recovery of CD4 counts and viral load failure, Addis Ababa, Ethiopia [43] and in Uganda study [44].…”
Section: Discussioncontrasting
confidence: 69%
“…Although this is the first ever national level analysis of CD4 count recovery data, this analysis confirms what smaller cohorts of up to 90 000 individuals from South Africa and other sub Saharan African settings have demonstrated. These studies demonstrated that i) the CD4 count at the start of ART was the strongest predictor of CD4 count recovery, [29] ii) CD4 recovery was rapid early in the course of ART but stabilised around 12 months post ART initiation, [30] and iii) CD4 count recovery is slower in males compared to females and in older individuals compared to younger individuals. [7,8,31,32] However, the comparison of CD4 count recovery by province and calendar year is new.…”
Section: Discussionmentioning
confidence: 99%